Linking environmental impact assessment and Positive Energy Districts: A literature review - Rosaria Volpe; Adriano Bisello; Andreas Tuerk; Francesco Guarino; Emanuela Giancola; Maria Nuria Sanchez; Giovanni Tumminia; Elisa Marrasso; Giovanna Pallotta; Emanuele Cutore; Maurizio Cellura; Alberto Fichera; et al. (Cleaner Environmental Systems)
This research delves into the environmental impact assessment of Positive Energy Districts (PEDs), focusing on comparative analyses of methodologies, key performance indicators, and an array of both theoretical and practical case studies. The literature review uncovers the strengths and weaknesses inherent current evaluation practices. The study reveals critical gaps in current assessment frameworks, particularly regarding the application to PEDs. It highlights the necessity for a holistic approach to PED evaluation, incorporating diverse energy sources and consumption patterns to fully understand their impact. The research advocates for the integration of multiple environmental factors in terms of innovative design and technology in PEDs, tailored to enhance both functionality and sustainability. It calls for the development of standardized guidelines and the learning from successful implementations to ensure the resilience and effectiveness of PEDs over time. Thus, this review paper aims to contribute to the body of knowledge on PEDs, offering insights and recommendations for future developments in this critical area of sustainable urban and energy planning.